FOREST EXPLOITATION AS REPRESENTED IN THE LORD OF THE RINGS: THE TWO TOWERS MOVIE - TAUFIQ, IVAN GAUZI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: forest exploitation, environment, The Lord Of The Rings: The TwoTowers movie. Forest exploitation threats ecosystem and causes a great damage to environment. One of the causes of the forest exploitation is greediness of authority by someone. The movie entitled The Lord of The Rings: The Two Towers reveals some causes and effects of forest exploitation caused by Saruman’s greediness of authority.This research applies Ecocriticism as an approach to analyze a movie entitled The Lord of The Rings: The Two Towers. This study also applies movie studies.The result of the study reveals that forest exploitation causes many effects to the environment. In the movie, Saruman as a wizard who becomes the main antagonist exploits all trees in the forest of Fangorn for his interest to win the war with human. The forest exploitation causes bad effects for three aspects such as forest, denizen, and environment around forest of Fangorn. Those effects cause imbalance to the cycle of ecosystem which disrupt the life of many living beings.For future researchers, it is advisable to conduct further studies on the same movie but with different approaches. One of the examples is Racism approach, because Racism approach can be used to analyze the reflection of Orcs as black people are slaved by Saruman.